2020
DOI: 10.1021/acs.energyfuels.0c01126
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Oxidation Kinetics of Iron(II) Thiochelate used as a Nitric Oxide Absorbent in Flue Gas

Abstract: Iron(II) thiochelates, especially iron(II) 2,3-bis(sulfanyl)propane-1-sulfonate (Fe(II)(DMPS) 2 ), have received particular attention as nitric oxide (NO) absorbents because they maintain high NO removal efficiency even in the presence of O 2 in flue gases. Herein, we explored the O 2 -inducing oxidation kinetics of Fe(II) and thiol groups (R−SH) in Fe(II)(DMPS) 2 and analyzed the resultant products to understand the resistive behavior toward O 2 . Quantitative analysis revealed that 4 mM of Fe(II) in 10 mM Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The voltammogram of Fe­(II)­(DMPS) 2 showed a pair of distinct redox peaks with the half-wave potential at E 1/2 = −0.115 V vs Ag/AgCl, while Fe­(III)­(DMPS) 2 displayed a much lower peak current density at a nearby potential. It is known that Fe­(III)­(DMPS) 2 undergoes autoreduction, during which Fe­(III) and DMPS in the complex react to generate a Fe­(II) and DMPS dimer linked by a disulfide (RS–SR) bond. , This chemical reaction is related to the breakage of the complex and could deteriorate the electrochemical activity of Fe­(III)­(DMPS) 2 . The discrepancy in the shape between the reduction and oxidation peaks was also noticeable, suggesting the different reduction and oxidation environments of Fe­(DMPS) 2 at the electrode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The voltammogram of Fe­(II)­(DMPS) 2 showed a pair of distinct redox peaks with the half-wave potential at E 1/2 = −0.115 V vs Ag/AgCl, while Fe­(III)­(DMPS) 2 displayed a much lower peak current density at a nearby potential. It is known that Fe­(III)­(DMPS) 2 undergoes autoreduction, during which Fe­(III) and DMPS in the complex react to generate a Fe­(II) and DMPS dimer linked by a disulfide (RS–SR) bond. , This chemical reaction is related to the breakage of the complex and could deteriorate the electrochemical activity of Fe­(III)­(DMPS) 2 . The discrepancy in the shape between the reduction and oxidation peaks was also noticeable, suggesting the different reduction and oxidation environments of Fe­(DMPS) 2 at the electrode.…”
Section: Resultsmentioning
confidence: 99%
“… In the group of iron­(II) chelate, thiochelate was proposed as a stable alternative to the most well-studied Fe­(II)­(EDTA), as it is less susceptible to the undesired oxidation of Fe­(II) to Fe­(III) by O 2 contained in flue gases (2–6% by volume) and has a higher NO absorption capacity (2.1 × 10 7 L mol –1 at 55 °C). , The representative thiol-containing ligand is 2,3-dimercapto-1-propanesulfonate (DMPS), which possesses two thiol groups in a molecule. We previously identified that its oxidation resistivity stems from the sacrificing oxidation of the thiol groups, thereby shielding Fe­(II) from O 2 -induced oxidation within the complex . The resultant oxidized iron thiochelate, however, eventually loses its binding affinity to NO; thus, the regeneration process must be accompanied to maintain the original NO binding capacity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One could refer to the recent review by Yang et al for discussions on the DeNO x methods such as SCR, SNCR, adsorption, storage reduction, and especially on direct catalytic decomposition of NO using catalysts involving noble metals, metal oxides, perovskite-type composite oxide, hydrotalcite materials, heteropoly acid, and Cu-ZSM-5. Various NO reduction chemical absorption systems have also been explored by different researchers using absorbents including Fe­(II)­EDTA, , Fe­(II) thiochelates, and 1,3-dimethylthiourea-derived eutectic solvents. , More specifically, abatement of NO x using SCR with ammonia is the most developed process because of its cost saving and efficiency in the presence of other competitive gases such as O 2 , H 2 O, and SO 2 . …”
Section: Introductionmentioning
confidence: 99%
“…Various NO reduction chemical absorption systems have also been explored by different researchers using absorbents including Fe(II)EDTA, 21,22 Fe(II) thiochelates, and 1,3-dimethylthiourea-derived eutectic solvents. 23,24 More specifically, abatement of NO x using SCR with ammonia is the most developed process because of its cost saving and efficiency in the presence of other competitive gases such as O 2 , H 2 O, and SO 2 . 25−27 Three types of catalyst have been developed and are commercially used: noble metal-based catalyst, mixed oxides (V 2 O 5 /TiO 2 ), and zeolites.…”
Section: Introductionmentioning
confidence: 99%